Midgut bacteria in deltamethrin-resistant, deltamethrin-susceptible, and field-caught populations of Plutella xylostella, and phenomics of the predominant midgut bacterium Enterococcus mundtii - Wenhong Li (Nature Portfolio, 2017)
Abstract Gut bacteria play a significant role in host insect. This study evaluated detail difference of midgut bacteria in deltamethrin-resistant, deltamethrin-susceptible and field-caught populations of diamondback moth, and studied phenomics of the predominant midgut bacterium Enterococcus mundtii. Cultivable bacteria revealed that E. mundtii and Carnobacterium maltaromaticum dominated the bacterial populations from deltamethrin-resistant and deltamethrin-susceptible larval midguts, whereas E. mundtii was predominant in field-caught population. Illumina sequencing analysis indicated that 97% of the midgut bacteria were from the phyla Firmicutes, Proteobacteria and Cyanobacteria. Both resistant and susceptible populations had more Enterococcus and Carnobacterium. Enterococcus, Carnobacterium, Bacillus, and Pseudomonas were predominant in the field-caught population. A phenomics analysis revealed that E. mundtii was able to metabolize 25.26% of the tested carbon sources, 100% of the nitrogen sources, 100% of the phosphorus sources and 97.14% of the sulfur sources, had a wide range of osmolytes and pH conditions, and showed active deaminase activity but no decarboxylase activity. This is the first report regarding different populations of DBM midgut bacteria analyzed using both high-throughput DNA sequencing and cultivation methods, and also first report concerning the phenomics of E. mundtii. The phenomics of E. mundtii provide a basis for the future study of gut bacteria functions.